2023
DOI: 10.3390/molecules28196988
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion of Lavandula angustifolia Essential Oil/Gold Nanoparticles: Antibacterial Effect against Multidrug-Resistant Wound-Causing Bacteria

Balqis A. Fadel,
Bassma H. Elwakil,
Esraa E. Fawzy
et al.

Abstract: Hospitalized patients are severely impacted by delayed wound healing. Recently, there has been a growing focus on enhancing wound healing using suitable dressings. Lavandula angustifolia essential oil (LEO) showed potential antibacterial, anti-inflammatory, and wound healing properties. However, the prepared gold nanoparticles possessed multifunctional properties. Consequently, the present investigation aimed to synthesize a novel nanosystem consisting of nano-Lavandula angustifolia essential oil and gold nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Of course, in this study examined the impact of LEO-NE for the first time on P. aeruginosa , which indicates its antimicrobial effects. In line with this study, Fadel et al (2023) examined the antibacterial properties of LEO-NE on Proteus mirabilis ( 28 ). The study conducted by Derya Demir et al in 2023 demonstrated the efficacy of lavandula in enhancing wound healing in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 53%
“…Of course, in this study examined the impact of LEO-NE for the first time on P. aeruginosa , which indicates its antimicrobial effects. In line with this study, Fadel et al (2023) examined the antibacterial properties of LEO-NE on Proteus mirabilis ( 28 ). The study conducted by Derya Demir et al in 2023 demonstrated the efficacy of lavandula in enhancing wound healing in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 53%
“…L-EO is derived from the blossoms of Lavandula angustifolia [252]. As described in Section 2.13, the major components of L-EO are linalool and linalyl acetate [107].…”
Section: Lavender-essential Oil (L-eo)mentioning
confidence: 99%
“…The recently produced formulation of nano-gold and nano-Lavandula angustifolia demonstrated complete eradication of pre-existing P. mirabilis biofilm. The MIC and minimum biofilm eradication concentration (MBEC) values for this formulation were determined to be 8 and 16 g/mL, respectively (Figure 2) (Fadel et al, 2023).…”
Section: Application Of Microemulsion Essential Oilmentioning
confidence: 99%